Empirical study of 3D-HPE on HOI4D egocentric vision dataset based on deep learning - Le, Van Hung (Universitas Ahmad Dahlan, 2024)
3D hand pose estimation (3D-HPE) is one of the tasks performed on data obtained from egocentric vision camera (EVC) such as hand detection, segmentation, and gesture recognition applied in fields such as HCI, HRI, VR, AR, Healthcare, supporting for the visually impaired people, etc. In these applications, hand point cloud data obtained from EV is not very challenging due to being obscured by gaze direction and other objects. Our paper performs a comparative study on 3D right-hand pose estimation (3D-R-HPE) from the HOI4D dataset with four cameras used to collect and animate the dataset. This is a very challenging dataset and was published at CVPR 2022. We use CNNs (P2PR PointNet, Hand PointNet, V2V-PoseNet, and HandFoldingNet - HFNet) to fine-tune the 3D-HPE model based on the point cloud data (PCD) of hand. The resulting error of 3D-HPE is presented as follows: P2PR PointNet (average error (Erra) is 32.71mm), Hand PointNet (average error (Erra) is 35.12mm), V2V-PoseNet (average error (Erra) is 26.32mm), and HFNet (average error (Erra) is 20.49mm). HFNet is the latest CNN (in 2021) with the best results. This estimation error is small and can be applied and modeled to automatically detect, estimate, and recognize hand pose from the data obtained by EV. The average processing time is 5.4fps when done on the GPU of the HFNet, which is the fastest. Detailed quantitative and qualitative results were presented that are beneficial to various applications such as human-computer interaction, virtual and augmented reality, and healthcare, particularly in challenging scenarios involving occlusions and complex datasets.